1992
DOI: 10.1177/104239159200400101
|View full text |Cite
|
Sign up to set email alerts
|

Smoke Venting By Gravity Roof Ventilators Under Windy Conditions

Abstract: The smoke extraction performance of gravity roof ventilators in the presence of wind is considered. A solution procedure which permits the determination of the hot layer depth for different interior and roof pressures is proposed. Negative roof pressure is shown to enhance extraction rate, while positive pressure tends to deepen the layer. Ventilators with low loss coefficient are found to perform better than an open pipe under windy conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Fire 2021, 4, x FOR PEER REVIEW 9 of 17 proved that FDS is capable of modelling flame spread and specifying the optimum measure for the combustible load substance. In 1992, Than [76] found that wind effects can increase smoke extraction as it produces negative pressures in roof ventilators (which are intensively applied in industrial structures to remove smoke, heat, contaminations and odors from the interiors of the structure). Window failure in an apartment fire in the presence of an external wind can lead to rapid and considerable growths in the fire's heat production.…”
Section: Fire-wind Interaction Effects On Low-rise Buildingmentioning
confidence: 99%
“…Fire 2021, 4, x FOR PEER REVIEW 9 of 17 proved that FDS is capable of modelling flame spread and specifying the optimum measure for the combustible load substance. In 1992, Than [76] found that wind effects can increase smoke extraction as it produces negative pressures in roof ventilators (which are intensively applied in industrial structures to remove smoke, heat, contaminations and odors from the interiors of the structure). Window failure in an apartment fire in the presence of an external wind can lead to rapid and considerable growths in the fire's heat production.…”
Section: Fire-wind Interaction Effects On Low-rise Buildingmentioning
confidence: 99%
“…This downward wind pressure might be greater than the upward pressure induced by buoyancy. Air pressure distribution inside and outside the atrium should be estimated carefully with reference to the literature results [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] in some projects. Therefore, there are concerns on the performance of static smoke exhaust systems, particulary in crowded deep underground subway stations or atrium buildings in high-density tall building areas [1,10,11].…”
Section: Introductionmentioning
confidence: 99%